Policing Reform in the South Korean Maritime Police After the Sewol Ferry Disaster. (May 2016) - Lim, Seunghoo; Moon, Jieun; Oh, Youngmin
Summary: The disbanding of the Maritime Police was the Korean President's political attempt to avoid blame after the Sewol ferry accident. Under the government reorganization bill, which was drafted by the government and submitted to the National Assembly, the Maritime Police will be renamed the Maritime Safety Agency and put under the control of the newly created ministry of national safety. Furthermore, the Maritime Police's investigation and intelligence functions will be transferred to the National Police Agency, and its roles of rescue operations and maritime security will be moved to the new national safety body. The reality of this policing reform is closer to "organization succession" than it is to "organization termination." Borrowing the concept of blame avoidance, we will examine the nature, causes, and consequences of the blame observed in this process of policing reform, which is intertwined with the historical background of the developmental state in South Korea. In this study, we expect to acquire important lessons about how the reformation of police organizations was used by the Korean government as an instrument for responding to disaster by providing new insights into the study of the complex forms of political interactions among multiple stakeholders in times of crisis. In particular, we will try to understand the causes and effects of this extreme case, the Sewol ferry accident, and the subsequent disintegration of the Maritime Police Agency through the perspective of the Korean police bureaucracy and the developmental states. Copyright © 2016 John Wiley & Sons, Ltd.